Aboriginal Students’ Achievement in Science Education: The Effect of Teaching Methods (Alberta Journal of Educational Research, 2010)
Some authors assume that the academic difficulties encountered by Aboriginal students can be partly explained by the discrepancy between teaching methods and Aboriginal learning styles. However, this hypothesis lacks empirical foundations. Using pan-Canadian data, we tried to identify the most efficient teaching methods for Aboriginal students and assessed whether these methods were associated with performance differences between Aboriginals and non-Aboriginals in science education. Results revealed that judicious dosage and a proper balance among teaching methods seem to be required for students’ optimal achievement. In addition, only marginal differences were observed between Aboriginals and non-Aboriginals. However, standard assessment methods might partly explain these unexpected results.